Improvement of Project Management in an SME - A Six Sigma Approach - Khelil, Abdulruhman; Vijay Kumar, Chetan (My University, 2024)
Enterprises all throughout the world, especially small and medium-sized businesses (SMEs), are essential to economies because they create jobs, innovate, and contribute value. However, in project based SMEs, because of their different structures, dispersed locations, and cultural barriers, SMEs especially those operating globally present distinct project management challenges because of their dynamic nature. This paper examines the project management difficulties that a developing medium-sized global organization has and suggests solutions to meet goals in the face of changing circumstances. Examining the existing information available on project oriented SMEs that work with project management and continuous improvement methodologies like Kaizen and Hoshin Kanri, this research investigates structural issues arising from growth and increasing targets. The methodology employed aligns with the Six Sigma DMAIC method, addressing research questions centered on project management challenges and pathways to achieving organizational objectives. The research finds out a few challenges affecting the Project Management such as lack of Standard Operating Procedures (SOPs) and other un sustainable growth plans causing stress to the employees. The study later on moves forward in bringing out the causes of these challenges and finally marks out the areas of improvement with some recommendations. Important findings point to organizational structural challenges that are in need for focused adjustments. The fundamental objective of the recommendations is to match short-term improvements with long-term objectives by using continuous improvement approaches and improving organizational control while preserving project flexibility. This study adds to our understanding of project management in SMEs, especially when it comes to international expansion, and offers practical advice for businesses trying to successfully manage growth-related obstacles.
Keywords: Small to Medium sized Enterprises; Project management; Underlying causes; Affinity interrelationship matrix; Effective scoping; Fishbone-diagram; Multivariate analysis